The Comparison of Using Roundtable Activity and Picture for Improving the Second Year Students’ Writing Skill at SMA Negeri 3 Palembang - Yuyun Hendrety (Jurnal Didascein Bahasa, 2016)
ABSTRACT: The objective of this study was to find out whether or not there were any significant differences in students’ writing skill achievement between those who used Roundtable Activity and those who used Picture. The population of the study was the second year students at the school in academic year 2003/2004. Stratified random sampling was used in choosing the sample. The total number of the sample was 98 students; 49 were in the experimental group and the rest were in the control group one. The non equivalent control group design was used in conducting this research. The students in the experimental group were taught by using Roundtable Activity as the medium while those in another group were taught by using picture. The instruments used in collecting the data were the English writing tests and questionnaire. The data obtained from the tests were analyzed using Chi-square analysis on the help of SPSS program for windows to find out the relationship between variables of Roundtable Activity and Picture to the students’ writing skill achievement. The students in experimental group tended to have more significant achievement in making paragraph writing than their peers in control group. They tended to be more active in using Roundtable Activity as one of the prewriting techniques in making paragraph writing. Based on the result of the questionnaire, the use of Roundtable Activity was acceptable and also applicable since it helped them to find ideas in the prewriting stage of making paragraph writing.Key words: roundatable activity, picture,writing skill.